World history : Volume II since 1500 - Duiker,William J. and Spielvogel,Jackson J. (Australia Cengage Learning, 2016)
From the dawn of civilization to the modern dilemmas of nation building in Africa and the Middle East, this book looks at the common challenges and experiences that unite the human past and inform the future. It uses colorful visuals, maps, and dramatic first-hand historical accounts to give readers a powerful perspective on the human experience.
Include Index Maps Illustration
Keywords: World history -- History, Modern